A combination of an antioxidant with a prebiotic exerts greater efficacy than either as a monotherapy on cognitive improvement in castrated-obese male rats - Titikorn Chunchai (2020)
© 2020, Springer Science+Business Media, LLC, part of Springer Nature. Previous studies by ourselves and others have demonstrated that both obesity and testosterone deprivation have been related to cognitive decline. We have also shown that a prebiotic and n-acetyl cysteine (NAC) improved cognitive dysfunction in obese rats and castrated-male rats. However, the effects of NAC, a prebiotic (inulin), and a combination of the two on cognition in castrated-obese rats has never been investigated. The hypothesis was that NAC and inulin attenuated cognitive decline in castrated-obese rats by improving gut dysbiosis, and decreasing oxidative stress, glial activation and apoptosis. Male Wistar rats (n = 36) were fed with either a normal diet (ND: n = 6) or a high-fat diet (HFD: n = 30) for twenty-eight weeks. The resultant obese rats had a bilateral orchiectomy (ORX) and were randomly divided into five subgroups (n = 6/ subgroup). Each subgroup was treated with one of five therapies: a vehicle; testosterone replacement (2 mg/kg/day); NAC (100 mg/kg); inulin (10%, w/w), or a combination of the NAC and inulin for four weeks. The results demonstrated that castrated-obese rats developed gut dysbiosis, metabolic disturbance, brain pathologies, and cognitive decline. All of the pathological conditions in the brain were ameliorated to an equal extent by testosterone replacement, NAC, and inulin supplementation. Interestingly, a combination of NAC and inulin had the greatest beneficial effect on cognitive function by synergistically reducing hippocampal inflammation and ameliorating glial dysmorphology. These findings suggest that a combination of NAC and inulin may confer the greatest benefits in improving cognitive function in castrated-obese male rats.